2012
DOI: 10.4049/jimmunol.1103387
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Human RANKL Complexed with Its Decoy Receptor Osteoprotegerin

Abstract: Receptor activator of NF-κB ligand (RANKL), its signaling receptor RANK, and its decoy receptor osteoprotegerin (OPG) constitute a molecular triad that is critical in regulating bone remodeling, and also plays multiple roles in the immune system. OPG binds RANKL directly to block its interaction with RANK. In this article, we report the 2.7-Å crystal structure of human RANKL trimer in complex with the N-terminal fragment of human OPG containing four cysteine-rich TNFR homologous domains (OPG-CRD). The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 50 publications
(57 reference statements)
5
102
0
Order By: Relevance
“…However, it has been shown that the homodimeric form of OPG exhibits a much greater higher affinity for the homotrimeric form of RANKL (Schneeweis et al 2005;Theoleyre et al 2006). More recently, the crystal structure of the interaction between RANKL and OPG was described (Luan et al 2012). In this study, the authors showed that OPG (Domains 1 to 4) is able to interact with RANKL in a 1:1 ratio, and blocks the accessibilities of important biding sites of RANKL to RANK.…”
Section: Rankl and Trail: Ligands From The Tnf Familymentioning
confidence: 87%
“…However, it has been shown that the homodimeric form of OPG exhibits a much greater higher affinity for the homotrimeric form of RANKL (Schneeweis et al 2005;Theoleyre et al 2006). More recently, the crystal structure of the interaction between RANKL and OPG was described (Luan et al 2012). In this study, the authors showed that OPG (Domains 1 to 4) is able to interact with RANKL in a 1:1 ratio, and blocks the accessibilities of important biding sites of RANKL to RANK.…”
Section: Rankl and Trail: Ligands From The Tnf Familymentioning
confidence: 87%
“…The recombinant plasmids pET-OPG1 and pET-OPG2 express the amino-terminal cysteine rich domains (D1-D4) which are necessary for binding to RANKL (15,16). The third recombinant plasmid, pET-OPG3, was designed to express the carboxy-terminal portion of the protein that contains two putative death domain homologous regions (D5 and D6) which have been related to cytotoxic signals in mammalian cells (15,17), and a heparin-binding region (D7). To verify protein expression we analyzed the whole cell extract by anti-His monoclonal antibody (moAb) immunoblotting.…”
Section: Expression and Purification Of Osteoprotegerin Recombinant Fmentioning
confidence: 99%
“…The corresponding receptor monomers bind on the outside at the interface between two ligand monomers ( Fig. 1) (17)(18)(19)(20)(21)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). This is critically important for receptor activation, as it ensures that only an intact trimeric ligand can trigger signaling because even the loss of a single ligand monomer results in the loss of two receptor-binding sites.…”
Section: A Trimeric Ligand Bound To Three Receptors Forms the Basic Umentioning
confidence: 99%